Defining transmedia narrative: problems and questions. Dialogue with Mary-Laure Ryan (ENTHYMEMA, 2011)
In this interview Mary-Laure Ryan faces some problems that arise from her definition of «transmedia narrative». Can every semiotic system tell stories? How can we elaborate a definition of «narrative» which accounts both for cognitive and semantic aspects? How can we dispense with the syntactic level if we need a definition of «narrativity» that suits every semiotic system? Answering these questions, Ryan deals with other proposals developed around the same theoretical problems, and points out a thought-provoking argument against Meir Sternberg’s functionalist definition of narrative.
Keywords: narrative sequence; narratology; transmedia narrative